Urbanization in Latin America: constraints and opportunities for child feeding and care - Ruel, Marie T. (United Nations University, 2000)
The principal aim of this paper is to describe the socio-economic context in which the topic of processed complementary feeding in Latin America should be examined. Data from CEPAL (Comisión Económica para América Latina y el Caribe) and from the Demographic Health Surveys (DHS) are used to review global trends in urban poverty and malnutrition in the region. The phenomena that are unique to urban life and that are likely to have an impact on child-care and feeding practices are reviewed using data from DHS for six Latin American countries. The issues examined include the higher levels of education and of labour force participation of urban women, the larger percentage of women who head households, and the potentially different family structure and social networks, which may affect the availability of substitute child care. Urban and rural differences in breastfeeding and complementary feeding patterns are also examined to improve our understanding of the potential constraints and opportunities for the promotion of processed complementary foods in Latin America. Programmatic issues that need to be considered in designing and targeting such interventions in largely urbanized Latin America are also discussed.